MANAJEMEN KEPALA SEKOLAH DALAM MEWUJUDKAN SEKOLAH ADIWIYATA (STUDI KASUS DI SD NEGERI 02 TANAH PAK LAMBIK KOTA PADANG PANJANG) - Basri Basri (IAIN Batusangkar, 2018)
This research to describe the management of the principal in realizing the adiwiyata school in SD Negeri 02 Tanah Pak Lambik Padang Panjang City. This study is qualitative. Data collection is done through observation, interview and documentation study. The results showed that in realizing the adiwiyata program at SD Negeri 02 Tanah Pak Lambik, various management functions were applied by the principal. Starting from the planning, organizing, implementation and control performed by the principal, then with the hard work of the principal and all related elements can be realized adiwiyata program di SD Negeri 02 Tanah Pak Lambik.